The accessible large-scale renewable energy potential and its projected influence on Tamil Nadu's grid stability - Chelladurai Chandarahasan; Edwin Sheeba Percis (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Due to its inherent geographical potential for wind/solar power and other renewable energy sources (RES) generation, Tamil Nadu is one of the pioneering Indian states in the early development and utilisation of RES. Tamil Nadu accounts for roughly 25% of India's total wind energy capacity. Increased penetration of RES in a power system indicates that RESs have replaced traditional power plants that have historically managed and stabilised the power system, resulting in novel power flow situations. Grid stability must be enhanced in light of the integration of large-scale RES into the grid. The purpose of this research is to analyse and evaluate the impact of large-scale integration of RES by examining mitigating methods from the most recent academic articles and technical reports in this field. This will aid in identifying the key risks affecting the network's stability margin as a result of the widespread integration of RES generation, allowing for a reasonable increase in the network's stability margin. The study's findings will also help to guide the selection of appropriate mitigation strategies. As the stability margin improves, the future fraction of RES additions to the Tamil Nadu extra high voltage (EHV) grid will be increased significantly.